Study of Some Mechanical Properties for Composite Material Reinforced with Ribbon (Journal of the College of Basic Education, 2023)
This Research Studied Tensile Strength , bending strength , Impact strength and hardness for Composite Material which have Unsaturated polyester as a Matrix Reinforced by Metal Ribbon and Ceramic Particles . The Results show an increase in Tensile and bending strength , Impact strength and Hardness after the adding of Metal Ribbon , and the Reinforcement will increasing with the Ribbon volume fraction.